Pengenalan Pola Hidup Sehat dan Bersih pada Siswa Sekolah Dasar Pancoran 3 Bondowoso Guna Mengatasi Stunting pada Usia Anak Sekolah Dasar - Puspito, Agung Nugroho; Ubaidillah, Mohammad; Suud, Hasbi Mubarak; Faiqah, Qazzalva Nidya; Kaylani, Gyzna Luzetta; Aliyah, Rachmah; Putri, Duety Nectarinia; Azzahra, Ajeng Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Bondowoso is one of the 3 cities with the highest stunting rates in East Java. This social project aims to introduce a healthy and clean lifestyle to elementary school students in Pancoran 3, Bondowoso Regency. to overcome the stunting often experienced by elementary school children, especially adolescent girls. In addition, this project also aims to change student behavior by implementing a healthy and clean lifestyle in everyday life. The research method used is conventional, which involves presentations, discussions, and practices on healthy and clean lifestyles with participants in grades 5 and 4 and aged 11- 12 years. This activity was carried out 4 times during October 2024. The study results showed that almost all elementary school students in Pancoran 3 understand healthy and clean lifestyles well, but many still do not understand how to apply healthy and clean lifestyles in everyday life.